2014
DOI: 10.1530/joe-13-0532
|View full text |Cite
|
Sign up to set email alerts
|

Daily exercise training protects against albuminuria and angiotensin converting enzyme 2 shedding in db/db diabetic mice

Abstract: Angiotensin II (Ang II) is involved in induction and progression of renal damage in diabetes. Angiotensin converting enzyme 2 (ACE2) is highly expressed in the kidney and has been shown to be renoprotective by degrading Ang II to Ang-(1–7). Disintegrin and Metalloproteinase (ADAM) 17 mediated shedding of renal ACE2 contribute to diabetic nephropathy pathogenesis. Lifestyle modification and metformin are recommended as initial therapies for most patients with type 2 diabetes. The aim of the study was to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 72 publications
6
44
2
Order By: Relevance
“…Our previous studies have shown increased shedding of enzymatically active renal ACE2 and NEP in the urine of type 2 diabetic mice (Chodavarapu et al, ; Somineni et al, ) and in type 2 diabetic patients (Gutta et al, ). We have also shown colocalization of ACE2 and ADAM 17 in the brush border of renal proximal tubules in Akita and db / db diabetic mice (Chodavarapu et al, ; Salem, Grobe, & Elased, ).…”
Section: Discussionmentioning
confidence: 91%
“…Our previous studies have shown increased shedding of enzymatically active renal ACE2 and NEP in the urine of type 2 diabetic mice (Chodavarapu et al, ; Somineni et al, ) and in type 2 diabetic patients (Gutta et al, ). We have also shown colocalization of ACE2 and ADAM 17 in the brush border of renal proximal tubules in Akita and db / db diabetic mice (Chodavarapu et al, ; Salem, Grobe, & Elased, ).…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, treatment of Akita type 1 diabetic mice with insulin normalized hyperglycemia, attenuated urinary ACE2 shedding, albuminuria, and renal ADAM17 expression (41). We have also reported that physical exercise training and/or metformin treatment of type 2 diabetic mice attenuated renal ADAM17 expression and shedding of urinary ACE2 (44). Recently, it was demonstrated that Ang II type 1 receptors promote ADAM17 mediated ACE2 shedding in hypertensive patients (54).…”
Section: Introductionmentioning
confidence: 85%
“…Diabetes mellitus is characterized by increased blood glucose, insulin and leptin levels (Somineni et al 2014) and by impaired nitric oxide (NO) homeostasis with reduced availability of NO (Baylis 2012;Masha et al 2011;Pollock and Pollock 2011), resulting in endothelial dysfunction, a critical mediator of diabetic vasculopathy (Sena et al 2013). NO is required for S-nitrosylation, i.e.…”
Section: Introductionmentioning
confidence: 99%